2020
DOI: 10.1029/2020wr027657
|View full text |Cite
|
Sign up to set email alerts
|

In‐Home Tap Water Consumption Trends Changed Among U.S. Children, but Not Adults, Between 2007 and 2016

Abstract: Despite evidence that tap water is often safer and cheaper than alternative sources, tap water is avoided when perceived to be unsafe. Therefore, we conducted the first nationally representative U.S. trends analysis of in‐home tap water avoidance between 2007 and 2016. We tested whether changes occurred during/after the Flint water crisis, and whether not drinking tap from one's main water source differed by age, race/ethnicity, and socioeconomic status across time. Finally, we tested whether tap water avoidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 51 publications
5
43
0
Order By: Relevance
“…It is critical to monitor trends in the lack of any tap water consumption beyond average mean intakes because this can provide a window into potential underlying water insecurity. Second, we also found that prevalence of any bottled water consumption on a given day was 25% higher in 2017-18 than 2013-14, supporting the recent trends of increasing bottled water intake in the US 12,27 .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…It is critical to monitor trends in the lack of any tap water consumption beyond average mean intakes because this can provide a window into potential underlying water insecurity. Second, we also found that prevalence of any bottled water consumption on a given day was 25% higher in 2017-18 than 2013-14, supporting the recent trends of increasing bottled water intake in the US 12,27 .…”
Section: Discussionsupporting
confidence: 79%
“…We adjusted for the range 21 of the following covariates: age (2-5, 6-11, 12-19, 20-39, 40-59, 60+), sex, federal income to poverty ratio (FIPR; ratio of family income to the federal poverty guideline 22 : £130%, 131-350%, >350%), household reference educational attainment (for children/adolescents; high school graduate/GED equivalent and some college were released combined) and educational attainment (for adults), and whether respondents were born in the US or not 12,19 .…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Non‐whites consumed bottled water at higher rates, particularly within Latino communities (Hobson et al, 2007). In the United States, nationally representative data from 2007 to 2016 showed that after the Flint water crisis, tap water avoidance increased, especially among Hispanic and non‐Hispanic black populations, and households in lower socio‐economic classes (Rosinger & Young, 2020). It is also evident that the bottled water industry has relied on—and in many cases has actively fostered—diminished trust in municipal delivery systems (Doria, 2006), using slick marketing campaigns to promote bottled water as “pure” and more healthful that tap water (Pacheco‐Vega, 2019; Zenner, 2018).…”
Section: Exposing Six Myths Of Household Water Insecuritymentioning
confidence: 99%
“…According to data from the National Health and Nutrition Examination Survey, rates of tap water avoidance are increasing, particularly following the Flint drinking water crisis which exposed Detroit residents to unsafe levels of lead, a potent neurotoxin (21,22) . While the majority of tap water in developed countries is regularly tested for safety by water suppliers, lead can still enter drinking water at the tap through lead-laced plumbing, solder or fixtures in older buildings.…”
Section: Invited Commentarymentioning
confidence: 99%